Peran Asas-Asas Umum Pemerintahan Yang Baik Dalam Penyelesaian Sengketa Tata Usaha Negara Dan Hukum Acara - Rayhan Zidane Indymadjid (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. Indonesia is a country that has a concept of people's welfare so that all aspects of people's lives and government can run properly. The purpose of this research is to be able to analyze the role of the principles of good governance in resolving state administrative disputes and procedural law. The research method used is the normative method and the type of qualitative data that is describing all phenomena and events that occur in society in order to obtain legal certainty with the legal norms that apply in Indonesia. while data collection uses literature study with materials from journal articles, scientific papers and other written works. With this research, it is hoped that it will be able to explain the development of the general principles of good governance and be able to analyze the role of state administrative justice in good governance.